Gender Equity Tensions in South Africa’s post-apartheid higher education: in defence of differentiation - Akala, B; Divala, JJ (South African Journal of Higher Education, 2016)
This paper presents a theoretical and thematic exploration of gender equity in post –apartheid South African higher education. The paper argues that while South African women played a very important role in the struggle for political liberation, the current situation in South Africa’s political, economic and education institutions seems to suggest that the effort they put in the struggle does not commemorate the gains thereafter. A majority of South Africa’s girls and women still struggle to access quality education and excel at most levels, which is a direct contravention of the Constitutional guarantee of equality for all who live in this great nation. Although the gender equity paradigm in South African higher education can be credited as having recorded some formidable achievements in terms of increased enrolment for female students especially Black women in higher education, a deliberate effort has to be made to shift attention from aggregations to impediments in order for the promise of equality and equity to be realized for those who experienced most barriers in accessing higher education, In the current South African context, one needs to deal with disadvantages that are perpetuated through the socio-economic positioning of families, the inability to use the language of power, content complexity, embedded institutional cultures and practices, among others. Key words: Gender, equity, higher education, Post- apartheid